The progesterone and estrogen modify the uterine prolactin and prolactin receptor expression of hyperprolactinemic mice. (9th October 2014) - do Amaral, Vinícius Cestari; Carvalho, Kátia Candido; Maciel, Gustavo Arantes Rosa; Simoncini, Tommaso; da Silva, Priscilla Ludovico; Marcondes, Rodrigo Rodrigues; Soares, José Maria; Baracat, Edmund Chada
Abstract: The aim of this study was to evaluate the effects of metoclopramide-induced hyperprolactinemia on the prolactin (PRL) and PRL receptor's expression in the uterus of mice. For this purpose, 49 Swiss mice were divided into the following groups: GrSS (non-ovariectomized mice given vehicle); GrMET (non-ovariectomized mice treated with metoclopramide); OvSS (ovariectomized mice given vehicle); OvMET (ovariectomized mice treated with metoclopramide); OvMET+17βE (ovariectomized mice treated with metoclopramide and 17β estradiol); OvMET+MP (ovariectomized mice treated with metoclopramide and micronized progesterone); OvMET+17βE+MP (ovariectomized mice treated with metoclopramide and a solution of 17β estradiol and micronized progesterone). Immunohistochemical analyzes were evaluated semi-quantitatively. Our results showed that GrMET, OvMET+MP, and OvMET+17βE+MP presented strong PRL expression. OvMET and OvMET+17βE presented mild reaction, while GrSS and OvSS presented weak reaction. Concerning PRL receptor, OvMET+MP and OvMET+17βE+MP showed strong reaction; GrMET, OvSS, and OvMET+17βE showed mild reaction; and GrSS and OvMET showed weak reaction. These findings suggest that progesterone alone or in combination with estrogen may increase the expression of uterine PRL and PRL receptor. Chinese abstract: 本研究目的是评估胃复安所致高催乳素血症小鼠的子宫催乳素 (PRL) 和 PRL 受体表达的影响。 49 个瑞士小鼠分为以下组： GrSS ( 非 去势小鼠赋形剂组 ) ； GrMET （ 非去势小鼠 胃复安治疗组 ) ； OvSS( 去势小鼠赋形剂组 ) ； OvMET( 去势小鼠 胃复安治疗组 ) ； OvMET+17βE ( 去 势小鼠 胃复安和 17β 雌二醇治疗组 ) ； OvMET + MP( 去势小鼠 胃复安和 微粒化 孕酮治疗 ) ； OvMET+17βE+MP （去势小鼠 胃复安、 17β 雌二醇和 微粒化 孕酮溶液治疗组 ) 。应用免疫组化法进行半定量测定。研究结果显示， GrMET ， OvMET + MP ， OvMET+17βE + MP 显示 PRL 强阳性表达。 OvMET 和 OvMET + +17βE 显示中等表达, 而 GrSS 和 OvSS 显示弱阳性表达。关于 PRL 受体， OvMET + MP 和 OvMET + 17βE + MP 显示强阳性表达； GrMET ， OvSS 和 OvMET + 17βE 显示中等表达，而 GrSS 和 OvMET 显示弱阳性表达。这些研究表明，孕酮单独或结合雌激素可能增加子宫 PRL 和 PRL 受体的表达。